Study of some immunological variables resulted from Balb/c mice injection with Hydatid cysts protoscolex antigens - A. O. Humide1 , Abbdalwahab Hussain2 , Ezeddin A. Albayyar3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Human cyst disease is a common epidemic disease between humans. The current study was carried out tostudy some of immunological parameters (the immunoglobins IgG, IgA, the complement proteins C3, C4,the MIF of PMNs cells, the reducing of NBT and the phagocytosis of Candida albicans) in the Balb/c miceinjected with antigen of protoscolex. By using (15) BALb/c mice and the antibodies IgG, IgA in addition tothe complements (C3, C4) that were measured as well as the Migration Inhibition Factor (MIF). The resultsshowed that there were significant differences in IgG (13458) mg/dl. IgA (4773) mg/dl, C3 (359.7) mg/dl,C4 (90.80) mg/dl levels with injection of 0.5 ml in muscle and the MIF levels (1.49) with injection of (0.75)ml. so between the test and the control up (p?0.05). This might be a good candidate for immunization anddiagnosis of Hydatid cysts in the intermediate host of E. granulosus.